MENINGKATKAN PEMAHAMAN DAN PEMBINAAN GENERASI MUDA BERBASIS NILAI AGAMA ISLAM DI DESA TEBING TINGGI - Rabbi, Hakki; Samin, Samin; M. Nurzen, M. Nurzen (Institut Agama Islam Negeri Kerinci, 2023)
This research aims to increase students' knowledge of thinking in society and form students' attitudes of love, social care and responsibility towards the progress of society and foster religious values ​​in society. The research was conducted using interviews and direct field observation. The results show that in carrying out the program students are very active in answering every question about religion, they have begun to be able to differentiate Tajwid and their reading has begun to improve. Mosque youth have also been brave in providing religious material and participating in providing religious material.